123 Kaposiform hemangioendothelioma with Kasabach-Merritt phenomenon in a neonate: Successful treatment with sirolimus. (11th October 2021) - Vukšić, Iva; Ćaleta, Tomislav; Džepina, Petra; Ninković, Dorotea; Buljević, Andrea Dasović; Filipović-Grčić, Boris; Benjak, Vesna; Ozretić, David; Gluščić, Ana Petrović; Bilić, Ernest; Radoš, Marko; Dessardo, Nada Sindičić; et al.
Abstract : Kaposiform hemangioendothelioma (KHE) is extremely rare, life-threatening vascular tumor with estimated incidence of 0.071 cases per 100.000 children. It is notably associated with Kasabach-Merritt phenomenon (KMP), a condition characterised by profound thrombocytopenia, hypofibrinogenemia, and elevated markers of coagulation activation (D-dimers or fibrin degradation products). Mortality is highly associated with degree of coagulopathy. Patients diagnosed prenatally appear to have increased disease severity. Optimal therapy for KHE is not known. Oral steroids and vincristine for patients with inoperable tumors is most commonly reported, but is associated with limited response and significant side effects. Sirolimus (rapamycin), a mammalian target of rapamycin (mTOR) inhibitor, is currently being tested in a prospective phase II clinical trial. Here we present a full-term newborn prenatally diagnosed with giant vascular tumor, affecting the lateral neck. He was delivered by elective C- section and initially presented with a firm, violaceous neck tumor 14x10 cm. Following the birth, he rapidly evolved to severe KMP. Despite endovascular embolisation performed immediately after birth, his coagulopathy worsened to life threatening hemorrhage (platelets 8, 000/μL, fibrinogen 0.8 g/L, D-dimer >10 mg/L, PT-INR 1.36, aPTT 26 s, Hb 80 g/L, Hct 23%), necessitating aggressive blood products replacement to maintain hemostasis. MRI and laboratory investigations strongly suggested the diagnosis of KHE/KMP. Biopsy was not attempted because of the potential risk of hemorrhage. He was vitally endangered with rapidly enlarging tumor size compromising airway patency, as well as the worsening coagulopathy triggered by platelet entrapment. As there were no response to corticosteroid and propranolol therapy, we elected to start sirolimus (0.8 mg/m2 per dose twice daily) along with tapering parenteral corticosteroids. This therapeutic approach led to remarkable resolution of consumptive coagulopathy with stepwise regression of tumor size. After 14 months of follow-up he remains on sirolimus without toxicity, the tumor is barely visible, and MRI showed remarkable reduction in the tumor size. Currently, no standard treatment guidelines exist for KHE/KMP because of their rare nature and lack of prospective trials. Our experience adds to a growing body of evidence suggesting that sirolimus in the treatment of high-risk KHE/KMP patients might be an efficacious and safe treatment option.